Progress in Identifying High Nature Value Montados: Impacts of Grazing on Hardwood Rangeland Biodiversity - Pinto-Correia, T. (2020)
Due to their complex structure and traditional low-intensity management, Portuguese oak woodland rangelands known as montados are often considered high nature value (HNV) farming systems, and as such, they may be deemed eligible for subsidies and incentives by governmental and nongovernmental agencies. Too little is known about how the HNV concept might be applied to conserve complex silvopastoral systems. These systems, due to their structural and functional complexity at multiple scales, tend to support high levels of biodiversity. Montados are in sharp decline as a result of the rapid specialization of land management that, through simplification, undermines multifunctionality. Understanding how changes in management influence these systems and their biodiversity is needed for prioritizing conservation efforts and for ensuring they remain HNV systems. On the basis of a field survey in 58 plots distributed among 29 paddocks on 17 farms, we conducted an integrated analysis of the relationship between grazing intensity and biodiversity in montados of similar biophysical and structural characteristics. Data on management were obtained through interviews, and biodiversity data (vegetation, macrofungi, birds, herpetofauna) were obtained through specific field protocols. Additional spatial data, such as soil characteristics, slope, land cover, and linear landscape elements, were also analyzed. The results show no overall biodiversity variation as a result of different management practices. However, different groups of species react differently to specific management practices, and within a pasture, grazing impacts are heterogenous. In low grazing intensity plots, macrofungi species richness was found to be higher, while bird species richness was lower. Using tree regeneration as proxy for montado sustainability, results show less tree regeneration in areas with higher forage quality and more intense grazing. Pathways for future progress are proposed, including creating areas within a paddock that attract grazing away from where regeneration is desired.